Medvrstniško nasilje, kot ga zaznavajo učitelji in učenci osnovne šole - Posnic, Katja; Košir, Katja (Revija za elementarno izobraževanje, 2016)
Bullying in Basic School: the Perspectives of Teachers and Pupils. The main purpose of our study was to investigate how basic school pupils and teachers perceive and understand bullying. The participants in the study were 58 teachers and 396 pupils in basic school. The results indicate that both teachers and pupils perceive verbal bullying as the most frequent form of bullying compared to physical and relational bullying. Pupils report perceiving more bullying than teachers. Both pupils and teachers perceive physical and verbal bullying as more serious forms of bullying compared to relational bullying and report feeling more empathy toward victims of these two forms of bullying. In addition, teachers report that they are more willing to intervene in cases of physical and verbal bullying. There are significant differences between pupils’ and teachers’ reports of the likelihood of teachers’ interventions in cases of bullying; compared to pupils teachers report a higher likelihood of their intervention.
Keywords: bullying; frequency; teachers; pupils; intervention